Analisis rasio keuangan untuk memprediksi financial distress pada perusahaan subsektor makanan dan minuman yang terdaftar di BEI 2015-2019 - Kingkin Vinda Lailana dewi (COMPETITIVE, 2022)
The purpose of this study was to analze the effect of liquidity,profitability, and leverage on the financial distress of the food and beverage sub sector manufacturing companies listed on the Indonesia Stoxk Exchange. The population in this study is the food and beverage sub sector companies listed on the Indonesia stock Exchange for 2015-2019 period. The sampling technique was purposive sampling method. The research ample was 13 manufacturing companies in the food and beverage sub sector listed on the Indonesia Stock Exchange. The data analysis method used is multiple linier analysis. The results showed that the liquidity variable measured using the current ratio (CR) had positive and significant effect on financial distress, the profitability variable measured using return on asset (ROA)has no significant effect on financial distress, and the measured leverage. Using the debt equity ratio (DER) has a positive and significant effect on financial distress conditions simultaneously, the variables of liquidity, profitability, and leverage have a significant effet on financial distress. Keywords: Liquidity, Profitability¸ Leverage, Financial Distress